Effect of Timbre on Goodness-of-Fit Ratings of Short Chord Sequences - Jimenez, Ivan; Kuusi, Tuire; Ojala, Juha; Czedik-Eysenberg, Isabella; Harrison, Peter; Chander, Aditya (University of California Press, 2025)
Previous research has found that instrument-like timbres (hereafter, timbres) can affect the Goodness-of-Fit (GoF) evaluations of cadences (Vuvan & Hughes, 2019). Here, we expand these findings by testing more timbres and chord sequences and analyzing a wide array of chordal and timbral variables. One hundred and thirty-five participants with varying levels of music training provided GoF ratings for 15 C-C-X chord sequences constructed with piano, clean electric guitar, and choir timbres. The third chord was a major, minor, major-minor seventh, or minor seventh chord. The ratings of choir stimuli were higher and their range narrower than the ratings for the other two timbres, regardless of music training. Additionally, the profile formed by the GoF ratings of the 15 choir stimuli was different from the profiles of the other two timbres. Further analyses provided detailed information about the effect of timbre as well as harmonic and melodic factors on the ratings. Attack was identified as a likely contributor to GoF ratings of choir stimuli being higher than the ratings of the other stimuli. Tonal contextuality (Leman, 2000), affected by diffuse partials, and the importance given to the soprano are discussed as two plausible explanations for the narrow range and other idiosyncrasies of the GoF ratings of the choir stimuli.
Keywords: sointuanalyysi; sointiväri; harmonia